Assessment of COVID-19 pandemic stress among health sciences students in a private university in South-West Nigeria - Adedeji, Peter Oluyemi; Oyedeji, Aarinola Precious; Olaogun, Adenike Ayobola; Adedeji, Oluwatosin Adewusi (Journal of Ideas in Health, 2021)
Background: COVID-19 pandemic has been reported to have psychological effects on various aspects of human life and segments of society. The study aimed to assess COVID-19 pandemic stress during and after lockdown among health sciences students at a private university in South-West, Nigeria. Method: A descriptive, cross-sectional web-based research was conducted in a private teaching hospital of a private university using a simple random sampling technique. The study instrument was a self-structured questionnaire containing sociodemographic details and questions adapted from the validated Perceived Stress Scale (PSS) by Sheldon Cohen regarding lectures during and after COVID-19 lockdown. Data were analyzed with the aid of SPSS version 26 software. Results: A total of 220 respondents were included in the study, with a mean age of 22.08±2.996. Most of the respondents were females (157, 71.4%) in their 4th-year level (37%). The participants had a high level of stress during (46.8%) COVID-19 lockdown than after the lockdown (29.1%), and statistical significance was observed between the perceived stress level during and after the COVID-19 lockdown (McNemar-Bowker’s value = 29.322, P =<0.001) at P<0.05. The female gender (B = 2.432, P = 0.03) and the respondents in 3rd year (B = -4.178, P = 0.035) had moderate stress during COVID-19 lockdown at P < 0.05. After the COVID-19 lockdown, the respondents in their 5th year had both moderate (B = -1.73, P = 0.022) and high (B = -2.08, P = 0.026) stress at p<0.05 respectively. The respondents of age groups 17-20 years (B = 3.28, P = 0.04) and 21-24 years (B = 2.93, P = 0.046) also had high stress at P <0.05 after the lockdown. Most respondents suggested reducing online lecture loads and lockdown in school as ways the university can help students cope with stress in case of repeat pandemic outbreaks in the future. Conclusion: This study concludes that the health science students experienced a high level of stress during the COVID-19 lockdown and moderate stress level after the lockdown was eased.